The head and neck cancer genome in the era of immunotherapy. (January 2021) - Wijetunga, N. Ari; Yu, Yao; Morris, Luc G.; Lee, Nancy; Riaz, Nadeem
Highlights: Some HNSCC respond well to immunotherapy, but most do not. We review the genomic aberrations in HPV− and HPV+ HNSCC. We describe the emerging field of immunogenomics. Abstract: The recent success of immunotherapy in head and neck squamous cell carcinoma (HNSCC) has necessitated a new perspective on the cancer genome. Here we review recent advances in the carcinogenesis and molecular genetics of HNSCC with an eye on their implications for cancer immunity. Newer sequencing technologies have recently facilitated dissection of the complex interaction between the HPV virus, tumor, host factors, and the tumor microenvironment (TME) that help shed light on how the immune system interacts with head and neck malignancies.